Best Practices: The Neuroscience Program at Central Michigan University - Dunbar, Gary L. (J Undergrad Neurosci Educ, 2015)
The original design of our program at Central Michigan University (CMU) and its evolving curriculum were directly influenced by Faculty for Undergraduate (FUN) workshops at Davidson College, Oberlin College, Trinity College, and Macalester College. The course content, laboratory exercises, and pedagogy used were informed by excellent articles in the Journal of Undergraduate Neuroscience Education (JUNE) and presentations at these FUN workshops and meetings over the years. Like the program at Baldwin-Wallace College, which was a previous winner of the Undergraduate Neuroscience Program of the Year Award, as selected by the Committee on Neuroscience Departments and Programs (CNDP) of the Society for Neuroscience (SfN, our program stresses the importance of inquiry-based, hands-on research experience for our undergraduates and utilizes a peer-mentoring system. A distinct advantage that is employed at CMU is the use of graduate student mentors, which allows us to expand our peer-mentorship to distinct research teams that are focused on a specific research project. Developing our program was not easy. The present manuscript reviews the long and arduous journey (including ways in which we navigated some difficult internal political issues) we made to build a strong program. Hopefully, this description may prove helpful for other evolving programs, in terms of avoiding certain pitfalls and overcoming obstacles, as well as selecting practices that have proven to be successful at our institution.